Location strategy within the dealer channel - Sikora, Stanley (Kansas State University, 2010)
In the world of fast paced competition with a focus on profits, small businesses are always looking for ways to stay ahead of their competition. One way to maintain the competitive advantage is to join forces with another small business that sells and services similar products. Mergers and acquisitions have been very common in agribusiness since the farm economy collapse in the early 1980s. Farms have been increasing in size, equipment has been growing in complexity with new technologies and size to keep up with growing farm size and equipment manufacturers are merging to create larger corporations that offer more solutions to the end user. Additionally, fewer machines are being purchased by growers and producers each year and the machines that are being purchased are able to do more than previous models. The new complexities require highly trained and skilled technicians to make repairs and service these machines. Farming practices continue to evolve with more limited- and no-till crop production. These factors are contributing to dealers forming larger multi-store operations with trade areas large enough to provide an adequate return on investment to attract the resources required to sell and support technologically advanced agricultural equipment. Large multi-store organizations support the requirement of customers by providing higher levels of customer service. As these large organizations increase in size they ensure a more sustainable business model with reduced fixed expenses leading to higher returns on sales and increased total sales. This study will examine two multi-store farm equipment farm equipment dealerships with a total of a total of eleven locations and make recommendations to create a merger of equals. The analysis will include a review of current sales data at each location and make recommendations for any new locations strategy using industry data as well. This information will help determine which locations should be eliminated or combined into single locations to reduce expenses. The study will also provide data to support implementing standard job pricing in the new organization. A new functional management structure will also be recommended to guide the new company towards increased sales revenues and position the organization for long term growth and sustainability.
Keywords: Strategy